2014
DOI: 10.1111/brv.12084
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary ecology of testicular function: size isn't everything

Abstract: Larger testes are considered the quintessential adaptation to sperm competition. However, the strong focus on testis size in evolutionary research risks ignoring other potentially adaptive features of testicular function, many of which will also be shaped by post-mating sexual selection. Here we advocate a more integrated research programme that simultaneously takes into account the developmental machinery of spermatogenesis and the various selection pressures that act on this machinery and its products. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 158 publications
(173 reference statements)
4
87
1
1
Order By: Relevance
“…A lot of comparative studies considered that relative testis size and sperm production were strongly correlated, and testis size would be a useful means of evaluating a male investment in sperm production 8. Compared to European and American people, testicular volumes of 13 ml in OA seemed to be atrophic in our study, but the testicular volumes of normal men also were 13 ml averagely (data not showed).…”
Section: Discussioncontrasting
confidence: 60%
“…A lot of comparative studies considered that relative testis size and sperm production were strongly correlated, and testis size would be a useful means of evaluating a male investment in sperm production 8. Compared to European and American people, testicular volumes of 13 ml in OA seemed to be atrophic in our study, but the testicular volumes of normal men also were 13 ml averagely (data not showed).…”
Section: Discussioncontrasting
confidence: 60%
“…Although we cannot currently draw any firm conclusions as to the exact reasons for these positive associations, there are at least three potential and nonmutually exclusive explanations. Therefore, larger testes might be better at replenishing sperm reserves (Ramm and Schärer 2014). Because testosterone is secreted by the Leydig cells in the interstitial tissue of the testes (Jorgensen 1992), relatively large testes may be able to produce more testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…However, mating success does not guarantee reproductive success: When females mate with multiple males during a reproductive period, the temporal and spatial overlap between ejaculates incites competition for fertilization among them and potentially enables females to bias fertilization success toward one or the other ejaculate, thereby extending both intra-and intersexual selection beyond copulation (Parker 1970;Eberhard 1996). Due to their intimate link to competitive fertilization success, sperm quantity and quality are particularly evident targets of postcopulatory sexual selection (Snook 2005;Gomendio et al 2006;Pizzari and Parker 2009;Simmons and Fitzpatrick 2012;Lüpold 2013;Fitzpatrick and Lüpold 2014), as are the size and efficiency of the testes that produce these sperm (Harcourt et al 1981;Byrne et al 2002;Lüpold et al 2009Lüpold et al , 2011Soulsbury 2010;Ramm and Schärer 2014;Parker 2016).…”
mentioning
confidence: 99%
“…In either case, the likely target of selection is the sperm-production capacity, which can be increased by enlarging testes and/or their efficiency (Parker and Pizzari 2010;Vahed and Parker 2012;Ramm and Schärer 2014).…”
Section: Introductionmentioning
confidence: 99%